Improving Health and Safety in the Informal Sector: Evidence from a Randomized Trial in Bangladesh - Asad Islam; Wang-Sheng Lee; Margaret Triyana; Xing Xia (Institute of Labor Economics (IZA), 2023)
Workers in small businesses in low- and middle-income countries are exposed to significant risks of occupational accidents and illnesses. A safe and healthy workplace could improve the productivity and sustainability of the business. In this paper, we conduct a randomized controlled trial in Bangladesh that provides informal firms with information on occupational health and safety (OHS) to improve their workplace practices. The intervention comprised two treatment arms: one focused solely on OHS training (the OHS arm), while the other offered business training and access to financing in addition to OHS training (the OHS+Biz arm). After two years, treated firms showed improvements in business practices, particularly those related to safety and a decent work environment. Moreover, both treatment arms experienced increased output and sales revenue. The OHS+Biz arm generally had no additional impact on firm outcomes compared to the OHS arm, suggesting that OHS information is the primary factor driving safer and healthier workplaces, which consequently can lead to better firm outcomes.
Keywords: J28; C93; J81; I15; M53; J24; O14; 330; occupational health and safety; enterprise training; randomized controlled trial; informal economy; information; credit access